IMPROVING STUDENTS 'INTENSIVE READING ON BAHASA INDONESIA STUDY WITH PQ4R STRATEGY AT THE FIFTH GRADE OF PRIMARY SCHOOL MIS KESUMA LKMD - Eka Oksani Harahap (UIN Sumatera Utara, 2018)
This study is a learning Bahasa Indonesia in PQ4R strategy to improve students intensive reading ability. The purpose of this study was to determine the thoroughness and the average student learning outcomes, as well as a significant increase in the ability of students after using the PQ4R strategy on Bahasa Indonesia study. The location of this research is MIS Kesuma LKMD. This is based due to low literacy and lack of attention of students in participating Bahasa Indonesia study. The subjects were fifth grade students of MIS Kesuma LKMD, with the total number of students were 27, and its object is the use of teaching PQ4R strategy in Bahasa Indonesia study. The instrument used is the field test and observation sheet. Based on the analysis that has been studied is obtained an increase in the results of the I cycle of 74,07 into 85,19 in the II cycle and the average student learning outcomes in the I cycle of 80,00 and 67,78 into a significant increase in the ability of students after using PQ4R strategy.Keywords: Strategy PQ4R, completeness and improved ability of students.